2018
DOI: 10.1177/0266666918767484
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to acceptance of information and communication technology in agricultural extension in Indonesia

Abstract: The use of information and communication technology (ICT) has become progressively widespread in various sectors including agriculture. This study investigated the barriers to the diffusion of ICT in agricultural extension. Further, the study examined the effect of barriers toward ICT acceptance in agricultural extension. A paper and pencil survey by mail was conducted to collect data from 355 respondents in the Greater Surakarta Region, Indonesia. The study discovered that individual barriers, cultural barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…ICT has simplified the creation, procurement, storage, arrangement, location, retrieval and transmission of information through electronic apparatuses (Haneefa and Shukkoor, 2010). The massive adoption of ICT has brought a worldwide change in information and knowledge creation and its transmission (Purnomo and Kusnandar, 2019). It has impacted not only our daily routine lives but also other segments of society – for example, railways, air travel, the banking sector, postal services, medical services, printing, electronic resources, the digitization of official papers, library resources, library networking, electronic commerce, trade and entertainment (Sinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ICT has simplified the creation, procurement, storage, arrangement, location, retrieval and transmission of information through electronic apparatuses (Haneefa and Shukkoor, 2010). The massive adoption of ICT has brought a worldwide change in information and knowledge creation and its transmission (Purnomo and Kusnandar, 2019). It has impacted not only our daily routine lives but also other segments of society – for example, railways, air travel, the banking sector, postal services, medical services, printing, electronic resources, the digitization of official papers, library resources, library networking, electronic commerce, trade and entertainment (Sinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main barriers to e-learning in Africa according to Adarkwah (2021), andStork et al (2013) are two-fold -access and affordability and the difficulty in attracting users. Despite these hindrances, students in developed countries continue to adjust their technological capacity to the demands of the new normal (Purnomo & Kusnandar, 2019;Stork et al, 2013). In effect, the pandemic increased the digital gap between vulnerable students and those who have.…”
Section: Challenges Of Ert Adoptionmentioning
confidence: 99%
“…We found that the deductive research articles, which dominate our samples, to some extent, have attempted to incorporate local context into their studies, with the main objective is to be "reporters" (Colquitt & Zapata-Phelan, 2007). We found that the authors have attempted to contextualize their variables such as culture in IT adoption (Purnomo & Kusnandar, 2019), organizational factors (Handayani et al, 2017), or individual/ human attitude (Batara et al, 2017;Kim & Park, 2018):…”
Section: To What Extent Indonesian Scholars Have Considered Context In Research?mentioning
confidence: 99%